The Relationship of Bag Load to Changes Vertebra Curves in Students (Study on Students Age 9-12 Years at SDIT Al Ikhlas, Magetan) - Andera Prastina Sukmawati; Arif Pristianto; Dwi Rosella Komalasari (P3M Universitas 'Aisyiyah Surakarta, 2023)
In children aged 9-12, reduced bone density, length of schooling, duration of daily bag use and bag weight exceeding the recommended weight of 10-15% of body weight can affect changes in the vertebral curve either into kyphosis, lordosis or scoliosis. The purpose of this study was to determine the relationship between bag load and changes in the vertebral curve as measured by the plumb line and scoliometer. The load of the bag is seen from 2 things, namely the weight of the bag and the duration of use of the bag. The research method used a cross sectional study with a sample of 207 school children aged 9-12 years using 2 analytical tests. The results of the Kendall's tau-b analysis test showed p-value = 0.773 and 0.262 (>0.005) which showed that there was no relationship between the weight and duration of bag use and changes in the vertebral curve. The results of the Spearman Rho test analysis showed p-value = 0.448 and 0.407 (> 0.005) which showed no relationship between weight and duration of bag use with the degree of change in the vertebral curve (Angle of Trunk Rotation/ATR).